PENGARUH SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN SHAMPOO PANTENE PADA PT. BORWITA CITRA PRIMA DEPO SITUBONDO - Rini Kartika Sari (Growth, 2018)
This study aims to determine whether there are effects simultaneously or partially between Supermarket and Grocery Stores Pantene Shampoo on sales volume, as well as the dominant variable effect between Self and Grocery Stores Pantene Shampoo on sales volume. The variables studied were, channel distribution (Supermarket and Grocery Stores), as independent variable (predictor) and dependent variable (dependent = response) is volume sales Pantene Shampoo at PT. Borwita Citra Prima Sub Branch Situbondo. Primary data obtained through interviews with the leaders (Supervisor) PT. Borwita Citra Prima Sub Branch Situbondo, while secondary data obtained through the study of literature, data from the number of agents and sales data furnished by other literature sources. Based on the analysis that has been done can be concluded that the first, simultaneously (together) note that the value of Fcount > Fmeans that Ho is rejected and Ha accepted which means no simultaneous effect between Supermarket and Grocery Stores Pantene Shampoo on sales volume. Second, note that the partial Supermarket and Grocery Stores equally possess tcount > ttable and probability of < 0,05, which means there is a partial effect on sales volume Pantene Shampoo. And third, the dominant variable Grocery Stores in influencing sales volume Pantene Shampoo. This is evident from the number of multiple linear regression coefficients for the Self (X1) of 1,385 and Grocery Stores (X2) of 2,219.